2022
DOI: 10.31580/pjmls.v5i2.2533
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mitscherlich–Bray Equation for Fertilizer Use on Raya

Abstract: Raya (Brassica juncea L.) as an imperative oilseed crop, necessitates a judicious amount of fertilizers for its sufficient yield, however the soils in Pakistan are becoming nutrient scarce owing to extensive farming. In order to evaluate the accurate fertilizer requirement for potential raya yields, an experiment was conducted at Regional agricultural research institute, Bahawalpur, Pakistan during the years 2018-2020. Various combinations of NPK fertilizers were made and applied to Raya crop. The treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Based on this scenario (R = 0.2, p = 0.008), the fertilizer P rates for aerobic rice calculated estimated to be 68.2, 62.8 and 57.3 kg ha -1 if the soil test value was 10, 15 and 20 kg ha -1 , respectively. This suggested that there is a dire need of site-specific nutrient management system rather than the generally adopted general recommendations that is made for large areas [13].…”
Section: Soil Test-based P Fertilizer Recommendations For Aerobic Ricementioning
confidence: 99%
“…Based on this scenario (R = 0.2, p = 0.008), the fertilizer P rates for aerobic rice calculated estimated to be 68.2, 62.8 and 57.3 kg ha -1 if the soil test value was 10, 15 and 20 kg ha -1 , respectively. This suggested that there is a dire need of site-specific nutrient management system rather than the generally adopted general recommendations that is made for large areas [13].…”
Section: Soil Test-based P Fertilizer Recommendations For Aerobic Ricementioning
confidence: 99%
“…It has been reported that the Mitscherlich-Bray equation [log(A-y) = logA-c1b1-cx] can be used for the Mitsherlich calibration equation, depending on the relationships between the KCl-extractable NO3-N content in the soil and the yield (Bray, 1945;Afzal et al, 2014, Sonar and Babhulkar, 2002, Ali et al, 2022. In this study, it was aimed to obtain the relationship between the amount of NH4 + NO3 -N extracted with KCl and the yield for the sunflower plant under rainfed conditions in Thrace Region, using the Mitscherlich-Bray equation.…”
mentioning
confidence: 99%